2015
DOI: 10.1007/s11060-015-1887-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-429 inhibits glioma invasion through BMK1 suppression

Abstract: The purpose of this research was to examine the relationship between big mitogen-activated protein kinase 1 (BMK1) and miRNA miR-429 and to determine the effect of miR-429 on glioma invasiveness. Immunohistochemistry was used to evaluate BMK1 expression in glioma tissues. Real-time PCR was used to measure the expression of miR-429 and other RNAs. Western blot was used to detect the expression of BMK1 and other related proteins. Wound healing, Matrigel invasion, and chemotaxis assays were performed to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Certainly other miRNAs can target PCDH8 such as miR-429, which has been shown to be a regulator of the epithelial-to-mesenchymal transitional during embryo implantation (43). miR-429 has been shown to inhibit glioma invasion through suppression of a big mitogen-activated protein kinase (44); however the link between miR-429 and STAT3 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly other miRNAs can target PCDH8 such as miR-429, which has been shown to be a regulator of the epithelial-to-mesenchymal transitional during embryo implantation (43). miR-429 has been shown to inhibit glioma invasion through suppression of a big mitogen-activated protein kinase (44); however the link between miR-429 and STAT3 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that miR-372 regulates GBM cell proliferation and invasion by directly targeting PHLPP2 (7). miR-210 upregulation inhibits proliferation and induces apoptosis in GBM cells by targeting SIN3A (8) and miR-429 inhibits GBM invasion through BMK1 suppression (9).…”
Section: Introductionmentioning
confidence: 99%
“…Promoter hypermethylation of tumour suppressor genes is a kind of epigenetic mechanisms in cancer cells [22]. Epigenetic modifications have been shown to be crucial mediators underlying in miRNA down-regulation and to display a tight correlation with carcinogenesis [16, 23]. Our data demonstrated that the hypermethylation of the upstream promoter of miR-507 led to the down-regulation of miR-507 in breast-cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 62%
“…Some tumor suppressor genes, such as miRNAs, can be down-regulated by promoter hypermethylation in human cancers [15, 16]. To elucidate the mechanism of miR-507 down-regulation, we performed BSP with genomic DNA to analyze the methylation level of miR-507.…”
Section: Resultsmentioning
confidence: 99%